Penanganan Assist Crew Maskapai Emirates oleh Unit Services pada PT Jasa Angkasa Semesta Bali - Amelia Dwi Agustin (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study looks into the handling procedures for Emirates Airlines assist crew carried out by the unit services at Bali’s I Gusti Ngurah Rai International Airport, operated by PT Jasa Angkasa Semesta. Assist crew handling is a crucial aspect of flight operations, ensuring that airline personel can transition efficiently and comfortably, which directly impacts the smooth flow of flight schedules. Unit services staff are responsible for providing comprehensive personalized assistance to airline crew. This is essential for minimizing potential obstacles and optimizing their mobility with the complex airport environment. The stages of assist crew handling are systematically designed to cover all phases of the crew’s journey from arrival to handover. This process begins with direct pick up of the crew at the terminal’s arrival gate or jet bridge area. This step ensures that the crew immediately receives guidance and assistance upon arrival at the airport. Unit services staff provide full direction and accompany to the crew during the immigration document check process. This assistance ensures compliance with immigration regulations, expedites entry into the country, and avoids unwanted delays. Staff also assist the crew with baggage claim in the baggage claim area, ensuring that the correct baggage is retrieved and assisting with handling. Futhermore, staff help with customs declarations and direct the crew for X-Ray baggage screening by customs officials. The assist crew handling process concludes with handling over the crew to the designated pick up, typically from the accommodation provider or transportation company responsible for the crew’s onward accommodation and movement. The results of this final report indicate that although the current procedures and stages of assist crew handling are functioning well, they can be improved by adding automated systems and enhancing staff services. The use of technology and good coordination are highly important for the provided services.
Entry oleh Arif 2026 Januari 29
Keywords: Assist Crew; Emirates Airlanes; Unit Services